Rapid Implementation of Outpatient Teleneurology in Rural Appalachia: Barriers and Disparities. Issue 3 (June 2021) - Strowd, Roy E.; Strauss, Lauren; Graham, Rachel; Dodenhoff, Kristen; Schreiber, Allysen; Thomson, Sharon; Ambrosini, Alexander; Thurman, Annie Madeline; Olszewski, Carly; Smith, L. Daniela; Cartwright, Michael S.; Guzik, Amy; et al.
Abstract : Objective: To describe rapid implementation of telehealth during the COVID-19 pandemic and assess for disparities in video visit implementation in the Appalachian region of the United States. Methods: A retrospective cohort of consecutive patients seen in the first 4 weeks of telehealth implementation was identified from the Neurology Ambulatory Practice at a large academic medical center. Telehealth visits defaulted to video, and when unable, phone-only visits were scheduled. Patients were divided into 2 groups based on the telehealth visit type: video or phone only. Clinical variables were collected from the electronic medical record including age, sex, race, insurance status, indication for visit, and rural-urban status. Barriers to scheduling video visits were collected at the time of scheduling. Patient satisfaction was obtained by structured postvisit telephone call. Results: Of 1, 011 telehealth patient visits, 44% were video and 56% phone only. Patients who completed a video visit were younger (39.7 vs 48.4 years, p < 0.001), more likely to be female (63% vs 55%, p < 0.007), be White or Caucasian ( p = 0.024), and not have Medicare or Medicaid insurance ( p < 0.001). The most common barrier to scheduling video visits was technology limitations (46%). Although patients from rural and urban communities were equally likely to be scheduled for video visits, patients from rural communities were more likely to consider future telehealth visits (55% vs 42%, p = 0.05). Conclusion: Rapid implementation of ambulatory telemedicine defaulting to video visits successfully expanded video telehealth. Emerging disparities were revealed, as older, male, Black patients with Medicare or Medicaid insurance were less likely to complete video visits.